The Andean cat Leopardus jacobita and other mammals in the priority site Andenes de Cuyocuyo, Puno, Peru - Maldonado, Willy (2022)
The Andean cat is one of the rarest cats in South America. Although it has a broad distribution in the Andes there are few reliable records and many sites whose presence has not been confirmed. The objective of this study was to confirm the presence of the Andean cat (Leopardus jacobita) in the Andenes of Cuyocuyo priority site, located in southeast Peru. In 2018, with an effort of 1275 camera-traps/day, 123 detections of 11 mammals were obtained, the most frequent being: Lagidium viscacia, Leopardus jacobita, Hippocamelus antisensis, and Leopardus garleppi. The relative abundance index of the Andean cat was 9.09 (N= 12, DE= 32.20) and the period of activity indicates that they have diurnal (Fr= 0.42) and nocturnal (Fr= 0.33) habits. The confirmation of the Andean cat in the priority site highlights the need to implement conservation mechanisms with the human communities that ensure the conservation of the Andean cat and other mammals in this region of Peru.